Closed-loop correction strategy for commutation deviation of BLDC motor based on internal power factor angle detection - Kun Liu; Wenjuan Zhang; Litao Dai; Jian Gao; Shoudao Huang (Energy Reports, 2023)
The first-order inertia of the armature winding of the brushless DC motor will cause current offset, which will reduce the electromagnetic torque. In the sensorless drive of brushless DC motors, correction of commutation point is an effective solution to improve motor performance. This paper analyzes the relationship between the electromagnetic torque and the compensation angle in the static coordinate system, and it is concluded that the internal power factor angle (IPFA) is equal before and after the commutation. The dc component of the IPFA is constructed as a feedback variable, a novel iterative sliding mode observer is designed to improve the compensation accuracy, and the adaptive output of the optimal angle is realized through the PI regulator. The scheme is simple to implement, and has higher accuracy, stronger adaptability and robustness. Simulation and experimental results verify the effectiveness and feasibility of the proposed correction strategy.